2010
DOI: 10.1093/jopart/muq043
|View full text |Cite
|
Sign up to set email alerts
|

Management Innovation and Organizational Performance: The Mediating Effect of Performance Management

Abstract: Management innovations (MIs) are widely adopted, but their influences on organizational performance are little researched in public settings. Positing that the MI-performance relationship is complex and is conditional over other characteristics of the organization, we examine the influence of MI on organizational performance both directly and indirectly through performance management (PM). PM is an important organizational process characteristic arising from public management reform and in itself influences pe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

10
321
6
40

Year Published

2011
2011
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 412 publications
(377 citation statements)
references
References 58 publications
10
321
6
40
Order By: Relevance
“…Table 6 The results of testing mediation with the use of Cohen and Cohen's method (Kraus et al 2012), but we should also note that some studies on the links between MI and organisational performance indicate the mediating role that different factors play in these relationships. In their study, Walker et al (2011) pointed to the variable of performance management, while Heij et al (2012) identified a mediating variable as exploratory and exploitative product and service innovations.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Table 6 The results of testing mediation with the use of Cohen and Cohen's method (Kraus et al 2012), but we should also note that some studies on the links between MI and organisational performance indicate the mediating role that different factors play in these relationships. In their study, Walker et al (2011) pointed to the variable of performance management, while Heij et al (2012) identified a mediating variable as exploratory and exploitative product and service innovations.…”
Section: Resultsmentioning
confidence: 99%
“…Mol and Birkinshaw (2009) underline that ''there are contrasting points of view in the literature about the impact of management innovation on firm performance''. The study of Walker et al (2011) shows that management innovation does not have an immediate effect on organizational performance (in the public sector); the impact of MI on organizational performance is fully mediated by performance management (2011, p. 379). Heij et al (2012) present similar results, confirming the existence of the relationships between management innovation and organizational performancethey are mediated by exploratory and exploitative product and service innovations.…”
Section: Management Innovationmentioning
confidence: 99%
See 1 more Smart Citation
“…Harper and Becker [13] indicated that innovation resulted in significant change-preferably an improvement in the real product, process, or service-that exceeds the impact of previous achievements; these authors further indicated that innovation supported sustainable business management. Firms encourage innovation to achieve production and marketing goals, to improve product or service quality, to lower their operational costs, to increase their market share, to attain production flexibility, and to improve the management process [14]. Previous studies have generally indicated that innovation was positively associated with business sustainability [15,16].…”
Section: Introductionmentioning
confidence: 99%
“…In other words, each successful experience with an innovative management practice may lead to adoption of a new one. On the other hand, by referring Moore and Hartley (2008), Walker et al (2010) put forth the idea of blurriness and dimensionality of innovation types in the public sector. The adoption of innovations may occur simultaneously instead of following a linear trajectory.…”
Section: Analyses and Resultsmentioning
confidence: 99%